Forgiveness and Christian ethics - Bash, Anthony (Cambridge Cambridge University Press, 2007)
What does it mean to forgive? The answer is widely assumed to be self-evident but critical analysis quickly reveals the complexities of the subject. Forgiveness has traditionally been the preserve of Christian theology, though in the last half century - and at an accelerating pace - psychologists, lawyers, politicians and moral philosophers have all been making an important contribution to questions about and our understanding of the subject. Anthony Bash offers a vigorous restatement of the Christian view of forgiveness in critical dialogue with those both within and without the Christian tradition. Forgiveness is a much more complicated subject than many theologians recognize. Bash explores the relevance of the theoretical discussion of the topic to recent events such as the Truth and Reconciliation Commission in South Africa, post-Holocaust trials, the aftermath of 9/11 and July 7 and various high-profile criminal cases.
Forgiveness and wrongdoing -- Forgiveness then and now -- Forgiveness and psychological therapy -- Justice and forgiveness -- Forgiveness and the New Testament -- The Ideal of forgiveness -- Forgiveness and structural wrongdoing -- Forgiveness, punishment, and justice -- Varieties of forgiveness -- Afterthoughts
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Forgiveness -- Religious aspects -- Christianity; Forgiveness -- Religious aspects -- Christianity; Christian Ethics; Forgiveness ; Religious aspects ; Christianity